2019
DOI: 10.1021/acsami.9b08285
|View full text |Cite
|
Sign up to set email alerts
|

Polypropylene Carbonate-Based Adaptive Buffer Layer for Stable Interfaces of Solid Polymer Lithium Metal Batteries

Abstract: Solid polymer electrolytes (SPEs) have the potential to enhance the safety and energy density of lithium batteries. However, poor interfacial contact between the lithium metal anode and SPE leads to high interfacial resistance and low specific capacity of the battery. In this work, we present a novel strategy to improve this solid–solid interface problem and maintain good interfacial contact during battery cycling by introducing an adaptive buffer layer (ABL) between the Li metal anode and SPE. The ABL consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…In fact, PPC has already been reported as a superb buffer layer in both solid‐state batteries and in liquid lithium metal batteries. [ 59–61 ] For example, Yang and co‐workers used PPC between PEO and Li and observed better contact and slower interfacial degradation. [ 61 ] Yue et al also reported similar results where they show PPC could enhance the compatibility of composite polymer electrolytes and Li.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, PPC has already been reported as a superb buffer layer in both solid‐state batteries and in liquid lithium metal batteries. [ 59–61 ] For example, Yang and co‐workers used PPC between PEO and Li and observed better contact and slower interfacial degradation. [ 61 ] Yue et al also reported similar results where they show PPC could enhance the compatibility of composite polymer electrolytes and Li.…”
Section: Resultsmentioning
confidence: 99%
“…[ 59–61 ] For example, Yang and co‐workers used PPC between PEO and Li and observed better contact and slower interfacial degradation. [ 61 ] Yue et al also reported similar results where they show PPC could enhance the compatibility of composite polymer electrolytes and Li. [ 62 ] In this work, we take a step further and show that, with the unique property of PPC, it can serve as a superb interphasial layer to block dendrites in polycrystalline ceramic solid electrolytes via the homogenizing effect.…”
Section: Resultsmentioning
confidence: 99%
“…The large volume changes of the anode during the Li plating/stripping process is also detrimental for the interface integrity, leading to insufficient cycling [30][31][32][33][34]. Therefore, approaches including polymer structural modification [35,36], optimizing the structure and proportion of Li salts [37,38], introducing organic plasticizers [39,40], and inorganic fillers [41,42] have been extensively explored for constructing a healthy anode/electrolyte interface between PEO-LiTFSI and Li metal.…”
Section: Introductionmentioning
confidence: 99%
“…Further improvement in the transference number (i. e., closer to unity) may be possible with a lower molecular weight PEG or stabilization of lithium metal SEI. An improved SEI, such as by the introduction of propylene carbonate oligomers [21] or other SEI‐forming organic and inorganic additives (e. g., fluoroethylene carbonate, LiNO 3 and LiBOB [22] ) would stabilize the electrode‐electrolyte interface and series resistance. Nevertheless, a higher lithium ion transference number value was measured with both plasticizers showing that the tethered anion approach holds promise for mitigating voltage droop problems.…”
Section: Resultsmentioning
confidence: 99%